The Discovery of Cold - Silver Mineralisation at Binebase, Sangihe Island, Indonesia - Alwan M (The Australasian Institute of Mining and Metallurgy, 1990)
At Binebase mineralisation is hosted within an andesitic Neogene volcaniclastic succession on Sangihe Island, Indonesia. Two major alteration types occur; an initial widespread phyllic assemblage of quartz -illite with chlorite, smectite, gypsum and pyrite, and a superimposed quartz - barite - sulphide assemblage. The phyllic alteration arose from a neutral to weakly acidic hydrothermal solution of greater than 200 degrees C, and the quartz - barite - sulphide assemblage arose from a cooler slightly more acidic fluid. This second alteration event is interpreted to have selectively replaced permeable volcaniclastic breccias and coarse lithic tuffs within the altered sequence. Gold and silver mineralisation is associated with the latter alteration, and is locally controlled by the degree of silicification and sulphide abundance. The sulphides present are pyrite, covellite and chalcopyrite. The sulphides are very fine grained with colloform and framboidal textures and were deposited contemporaneously with the bulk silicification of the coarse sediments. A large portion of the mineralised rock has been oxidised to a quartz - barite -limonite - goethite - jarosite assemblage.Coincident gold, silver and antimony geochemical soil anomalies gave the best correlation with anomalous gold and silver grades in bedrock as identified by drilling. Resistivity proved a reliable geophysical method for delineating zones of silicification.